Primary angioplasty and pharmaco-invasive strategies in the treatment of ST-elevated myocardial infarction - M. G. Glezer; E. I. Astashkin (Кардиоваскулярная терапия и профилактика)
The lecture is devoted to the choice of tactics and the rules of reperfusion therapy for ST-elevated myocardial infarction. Since the time of reperfusion is crucial for the survival of these patients and the preservation of a viable myocardium, proper organization of care and strict adherence to the guidelines for drug-induced and non-drug interventions is necessary. The lecture substantiates the tactics of pharmaco-invasive intervention, the choice of thrombolytic agent, provides data on indications and contraindications for thrombolytic therapy, dosing regimen of thrombolytic drugs, other antiplatelet and anticoagulant drugs required for reperfusion. Knowledge of current guidelines should help reduce ischemia time and cases of unjustified refusal to effective interventions.